2010
DOI: 10.1111/j.1365-2869.2009.00757.x
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde effects of triazolam and zolpidem on sleep-dependent motor learning in humans

Abstract: SUMMAR Y Drugs that act as allosteric activators at the benzodiazepine site of the gammaaminobutyric acid (GABA A ) receptor complex are used commonly to treat insomnia but relatively little is known of how such use affects learning and memory. Although anterograde effects on memory acquisition have been shown, possible retrograde effects on consolidation are more relevant when such agents are administered at bedtime. We tested the effects of two GABA A allosteric activators on sleep-dependent motor skill memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…In rats, administration of the GABA A agonists eszopiclone and zolipem after learning before sleep impaired contextual memory tested 24 h later (577). Two more recent studies in humans showed similarly impairing effects of triazolam and zolpidem on sleep-dependent consolidation of finger sequence tapping skills (835,836). This is remarkable, as the impairment in motor skill consolidation was paralleled by robust increases in the amount of non-REM sleep stage 2 and spindle activity as well as REM sleep in these studies.…”
Section: Gabamentioning
confidence: 89%
“…In rats, administration of the GABA A agonists eszopiclone and zolipem after learning before sleep impaired contextual memory tested 24 h later (577). Two more recent studies in humans showed similarly impairing effects of triazolam and zolpidem on sleep-dependent consolidation of finger sequence tapping skills (835,836). This is remarkable, as the impairment in motor skill consolidation was paralleled by robust increases in the amount of non-REM sleep stage 2 and spindle activity as well as REM sleep in these studies.…”
Section: Gabamentioning
confidence: 89%
“…However, numerous adverse effects associated with ZOL usage have been reported including driving impairment (Verster et al, 2006; Gunja, 2013), effects on balance and postural tone (Zammit et al, 2008), interference with memory consolidation (Balkin et al, 1992; Wesensten et al, 1996, 2005; Mintzer and Griffiths, 1999; Morgan et al, 2010) and increased incidence of complex behaviors during sleep (Hoever et al, 2010). Some studies investigated the effects of daytime administration of ZOL and tested psychomotor function upon arousal from naps (Wesensten et al, 2005; Storm et al, 2007), a protocol which our experiments closely mimic.…”
Section: Discussionmentioning
confidence: 99%
“…5,21 In this test, subjects are asked to type a 5-digit number sequence as quickly and as accurately as possible with the fingers of the nondominant hand by pressing 4 adjacent numeric keys on a standard computer keyboard. Subjects are instructed to look at the number sequence displayed on the computer screen while typing.…”
Section: Dependent Measuresmentioning
confidence: 99%
“…Finally, Morgan et al reported significant impairment of sleep-dependent memory on a motor task with triazolam (0.375 mg), but not with zolpidem immediate release (10 mg). 21 However, the dose of triazolam is rather high and the detected effect may be a direct influence of drug on motor performance during the morning testing period, rather than interference with SDMC. Additionally, the small sample (N = 12) may have provided insufficient power to detect an effect with the dose of zolpidem employed.…”
Section: Introductionmentioning
confidence: 99%